EKSPLORASI MIKORIZA ARBUSKULA INDIGENOUS PADA RHIZOSFER VEGETASI LAHAN PASCATAMBANG BATUBARA - Muhammad Hadi Prayoga; Budi Prasetya (Jurnal Tanah dan Sumberdaya Lahan, 2021)
Different types of vegetation have the potential to affect a type of spore, the number of spores, and the level of colonization in the roots. This study aims to determine the diversity of genus and the number of arbuscular mycorrhizal spores as well as the level of colonization in the vegetation of Bull Grass (Paspalum conjugatum Berg), Kemunting (Rhodomyrtus tomentosa), and Kirinyuh (Chromolaena odorata L) on post-coal mining land in Margomulyo Village, Kutai Kartanegara, Kalimantan. East. The research was conducted from February to October 2020. Sampling was carried out by purposive sampling based on the land cover area of the Bull grass, Kemunting, and Kirinyuh vegetation with four replications. Laboratory analysis was conducted in Biology Laboratory, Department of Soil Science, Faculty of Agriculture, Brawijaya University and chemical analysis of soil at the Laboratory of Soil, Faculty of Agriculture, University of Muhammadiyah Malang. The results showed that the genus Glomus was found from each of these vegetations with the number of spores in the Bull grass, Kemunting, and Kirinyuh vegetation, respectively 196 spores, 122 spores, and 100 spores per 100 g of soil, and the level of colonization in these vegetations respectively 83.33%, 63.33%, and 51.50%.